Pengaruh Desain Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. PLN (Persero) UP3 Palembang ULP Rivai - Pamungkas, Gerin Harya; Darwin, Darwin; Heriyanto, Heriyanto; Melita, Dina (CV. ITTC INDONESIA, 2024)
This study aims to examine the effect of Work Design on Employee Performance at PT PLN (Persero) UP3 Palembang ULP Rivai, the effect of Work Discipline on Employee Performance at PT PLN (Persero) UP3 Palembang ULP Rivai, and the combined effect of Work Design and Work Discipline on Employee Performance at PT PLN (Persero) UP3 Palembang ULP Rivai. This study involved 95 employees of PT PLN (Persero) UP3 Palembang ULP Rivai as respondents. Data were collected through questionnaires. The research method used was quantitative, with validity test, reliability test, classical assumption test, multiple linear regression analysis, coefficient of determination, t test, and f test. The results of the study showed that partially, Work Design and Work Discipline each have a significant effect on employee performance. Simultaneously, Work Design and Work Discipline also have a significant effect on employee performance at PT PLN (Persero) UP3 Palembang ULP Rivai.